2020
DOI: 10.1111/ppl.13248
|View full text |Cite
|
Sign up to set email alerts
|

Different drought resistance mechanisms between two buckwheat speciesFagopyrum esculentumandFagopyrum tataricum

Abstract: Water availability is one of the main factors affecting crop production and the occurrence of drought periods is expected to increase in the context of ongoing climate change. We investigated the impact of water stress on two pseudocereal species, common buckwheat (Fagopyrum esculentum) and Tartary buckwheat (Fagopyrum tataricum). Plants were grown under greenhouse conditions under two water regimes: control (40-50% soil humidity) and water stress (<20% soil humidity). Although closely related, both species di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 51 publications
2
18
1
Order By: Relevance
“…I. glandulifera plants were relatively tolerant to higher temperatures during their vegetative phase, as only physiological parameters such as SLA and stomatal conductance were lower at 27 • C. As higher temperatures did not affect leaf water content, reduced SLA is most likely attributable to a reduction in leaf size, which has been reported under similar conditions in other plant species [52]. In agreement, cell elongation becomes impaired when temperatures exceed the optimum for plant growth [53].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…I. glandulifera plants were relatively tolerant to higher temperatures during their vegetative phase, as only physiological parameters such as SLA and stomatal conductance were lower at 27 • C. As higher temperatures did not affect leaf water content, reduced SLA is most likely attributable to a reduction in leaf size, which has been reported under similar conditions in other plant species [52]. In agreement, cell elongation becomes impaired when temperatures exceed the optimum for plant growth [53].…”
Section: Discussionsupporting
confidence: 72%
“…Stomatal responses vary greatly between plant species [ 51 ]. For example, drought did not affect stomatal conductance in other species such as Tartary buckwheat ( Fagopyrum tataricum ) and starflower ( Borago officinalis ) [ 12 , 52 ]. Leaf water content remained constant between well-watered and drought-stressed plants and specific leaf area was neither affected by water stress.…”
Section: Discussionmentioning
confidence: 99%
“…Although F. tataricum was reported to be widely adaptable to hostile environments [ 43 ], its physiology and response to abiotic stress remain largely unknown. In previous studies, we compared the response of F. esculentum and F. tataricum to high temperature [ 44 ] and water stress [ 45 ]. High temperature mainly affected the reproductive stage and increased the antioxidant concentration in the two buckwheat species [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…High temperature mainly affected the reproductive stage and increased the antioxidant concentration in the two buckwheat species [ 44 ]. However, both species differed in their strategy to cope with water stress [ 45 ]. Vegetative and reproductive growth was less affected in F. tataricum than in F. esculentum , and it was suggested that F. tataricum exhibited traits of drought tolerance [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…F. tataricum frequently grows in poor quality soil including soils with increased salinity and H 2 O 2 can alleviate the negative impacts of salt stress on seed germination. At present, there are few studies that investigate the effect of H 2 O 2 seed soaking on the germination characteristics of F. tataricum seeds under salt stress [ 16 , 17 ]. We soaked F. tataricum seeds in different concentrations of H 2 O 2 to examine the germination characteristics, seedling growth, antioxidant enzyme activity, membrane lipid peroxidation, and osmotic adjustment substances present in seeds under salt stress.…”
Section: Introductionmentioning
confidence: 99%